Effect of fish meal substitution with fermented chicken feather meal in the diet on the growth of barramundi (Lates calcarifer) - Salamah Salamah; Anjani Dara Puspita; Munawwar Khalil; Mainisa Mainisa; Eva Ayuzar (Universitas Malikussaleh, 2026)
Chicken feathers contain about 80–90% protein, but the keratin type is poorly digestible, requiring fermentation. This study aimed to analyze the effect of substituting fish meal with fermented feather meal on the growth and survival of barramundi (Lates calcarifer). The research was conducted from March 8 to April 5, 2025, at the Hatchery and Aquaculture Technology Laboratory, Malikussaleh University. A Completely Randomized Design (CRD) with five treatments and three replications was used: A (0%), B (5%), C (10%), D (15%), and E (20%) substitution levels of fermented feather meal. Parameters observed included feed response, absolute growth in length and weight, feed conversion ratio (FCR), survival rate (SR), water quality, and feed proximate and organoleptic tests. The results showed that substituting fish meal with fermented feather meal significantly affected growth and feed efficiency (P<0.05). The best results were obtained in treatment D (15%) with an average length of 2.02 cm, weight of 2.28 g, FCR of 1.56, and survival rate of 83.33%. Water quality parameters remained within optimal ranges: temperature 25.8–29.1°C, pH 7–8.8, DO 4.6–6.44 ppm, and salinity 15 ppt. Keywords: Barramundi; Chicken Feather Meal; Fermented; Feed; Growth